The Development of Learning Media Using Powtoon for Junior High School - Sakti, Irma; Napsawati, Napsawati (Jurnal Pendidikan Fisika, 2021)
This study aims to develop learning media using Powtoon and to determine students’ responses. This type of research employed a 4-D development model developed by Thiagarajan with 4 stages, namely: defining, designing, developing, and disseminating stages. The research subjects were 25 students at SMP Ittihad Makassat in the academic year of 2020/2021. The research instrument includes a questionnaire in the form of a validation sheet and a student response sheet. The results of the study were obtained from material experts, media experts, and physics teachers with percentages of 87.5%, 80%, 83.2% respectively and have met the “very valid” criteria. The results of the questionnaire response analysis of students showed that the students’ response score was 3.93 or 78.67%, being in the “good” category. Therefore, it can be concluded that the learning media using Powtoon which was developed on the subject of light is very valid to use and get good responses from students.